Sensor for Quantitative Analytical Determination of Sulphite in Wine Using a System of Modified Electrode and a Membrane Absorption System - Aguirre-Quintana, M; Aguirre-Quintana, M; Romero-Figueroa, J; Arce-Escobar, R; Arce-Escobar, R (Electrochemical Society Inc., 2014)
In this work we present the comparison among three glassy carbon electrodes modified by Co-porphyrin (CoTAPP), orthophenylendiamine (OPD), or both, simultaneously. This comparison shows the differences among their electrochemical behavior and their electrocatalytic behavior toward the oxidation of sulfite. In the case of the glassy carbon modified electrodes, the presence of the copolymer enhances the electrocatalytic performance of the modified electrodes in spite of the non-catalytic response (compared to the bare glassy carbon) of both homopolymersmodified electrodes toward the oxidation of sulfite. Also, the oxidation of sulfite extracted from red wine is showed. The copolymer-modified electrode is capable of oxidizing the extracted free sulfite in a 0.02 M NaOH solution. Through the addition of standards method, a concentration of 44 ppm for free sulfite is found in a Chilean red wine. © The Electrochemical Society.